THEORETICAL FOUNDATIONS OF CROSS-BORDER PARALLEL PROCEEDINGS: THE CONCEPT AND CAUSES OF OCCURRENCE - FEDOROV A.S. (Legal Bulletin)
Cross-border litigation has become an important part of companies’ international economic activities. For this reason, the problem of parallel proceedings is critical, because they cause a conflict of jurisdictions and greatly impede the settlement of the dispute. The purpose of this study is to define the concept, features, types, and main reasons of the occurrence of parallel proceedings in international civil procedure. Within the framework of this goal, the problem of defining a “real" parallel proceeding and what criteria it must be met for its occurrence was studied. In addition, the relationship between the concept of “parallel proceedings" and the doctrine of “lis alibi pendens" was examined. Finally, the author analyzed the objective and subjective reasons of the occurrence of parallel proceedings and their specific features. In the work author predominantly uses dialectical and logical method, as well as analysis and synthesis. In the article, the author uses scientific papers of Russian and foreign scientists on this topic, judicial practice and legal acts. As a result of the study, it was concluded that parallel proceedings are judicial proceedings in several jurisdictions based on identical claims, the obligatory conditions of which are identical claims and parties of the dispute. The reasons for the occurrence of parallel proceedings are very diverse and caused by various factors, but the abuse of the right of a party to a parallel dispute is the most negative of them.